International comparability of statistics on income distribution - McGranahan, Donald (UN Research Institute for Social Development GenevaCH, 1979)
Reviews the current state of income distribution statistics and concludes that poor quality data and unresolved conceptual and technical problems, in a context of structural diferences among countries, do not permit valid cross-national comparisons at the present time.